A behavior-oriented formula to predict coastal bathymetry evolution caused by coastal engineering. (1st March 2017) - Chen, Dake; Wang, Yigang; Huang, Huiming; Chen, Cheng; Yuan, Chunguang
Abstract: The two common expressions of near-bed sediment flux (also called erosion and deposition flux) in terms of sediment carrying capacity and bed shear stress are unified in this study. A behavior-oriented formula to calculate coastal bathymetry evolution caused by coastal engineering on a muddy coast is also developed based on the unified expression. Compared with the other common behavior-oriented formulas on a muddy coast, the vertical suspended sediment distribution and near-bed sediment exchange mechanism are considered, and the formula has the advantage of calculating both bed siltation and erosion distribution. The formula is applied to simulate the local morphology change resulting from the siltation-promoting works at the mouth of the Yangtze River estuary of China. A comparison between the measurement and the calculated results of other common formulas shows that the morphology change caused by the project is well reproduced, and the behavior-oriented formula can be used to predict the coastal bathymetry evolution caused by coastal engineering on muddy coast.